Examining the role of needs support in mediating the relationship between programme quality and developmental outcomes in youth sport†. Issue 4 (4th July 2019) - Bean, Corliss; Forneris, Tanya
Abstract : Understanding how programme quality and needs support influence youth's psychosocial development within sport programming is critical given the abundance of postulations, yet lack of empirical evidence, that recognise the potential influence these variables have on youth developmental outcomes. The purpose of this study was two-fold: (a) to examine the role that programme quality and basic needs support played in psychosocial outcomes in youth sport and (b) to investigate if basic needs support mediated the relationship between programme quality and psychosocial outcomes. It was hypothesised that programme quality and needs support would independently contribute to psychosocial outcomes and that programme quality would positively predict psychosocial outcomes and needs support would mediate this relationship. A total of 214 youth ( M age = 14.26, SD = 1.88; 61 male, 153 female) completed three questionnaires at two time points that assessed the study variables. To examine the first purpose, structural equation modelling was used. Programme quality and needs support (measured at Time 1) significantly predicted psychosocial outcomes (measured at Time 2) independently. To investigate the second study purpose, bootstrapping analysis was used to test if needs support mediated this relationship. Results indicated that needs support partially mediated the relationship between programme quality and psychosocial outcomes. Findings provide initial evidence of the importance of delivering high-quality programmes that support basic psychological needs in order to foster psychosocial development in youth. Applied implications and future research areas are discussed.